2019
DOI: 10.3390/agronomy9060303
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Protocol for the In Vitro Plantlet Production of Caper (Capparis orientalis Veill.) from the East Adriatic Coast

Abstract: Caper (Capparis orientalis Veill.) is a species rich in bioactive compounds, with positive effects on human health. It has a great adaptability to harsh environments and an exceptional ability to extract water from dry soils. In Croatia, the caper grows as a wild plant, and its cultivation is insignificant, which is probably due to propagation difficulties. Micropropagation could be a solution for this. The aim of this study was to investigate the success of the micropropagation, in vitro rooting, and acclimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Among the tested auxins, NAA, alone or in combination with IBA, was more effective than IBA and IAA. As far as carbon source supplemented to the rooting media is regarded, sucrose generally resulted to be more effective than fructose, confirming what suggested by other authors that sucrose should be the carbohydrate of choice for caper in vitro propagation [25].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Among the tested auxins, NAA, alone or in combination with IBA, was more effective than IBA and IAA. As far as carbon source supplemented to the rooting media is regarded, sucrose generally resulted to be more effective than fructose, confirming what suggested by other authors that sucrose should be the carbohydrate of choice for caper in vitro propagation [25].…”
Section: Resultssupporting
confidence: 85%
“…In another Capparis species, such as C. decidua, best rooting was achieved on a medium supplemented with IBA (1 mg L −1 ) [16], but in a subsequent work of the same authors [31] 1.0 mg L −1 IBA combined with 0.5 mg L −1 IAA was considered better, whereas Deora and Shekhawat [15] found that 60-70% of the shoots rooted when pulse treated with 100 mg L −1 IBA. In another species (C. orientalis), closely related to C. spinosa, the highest rooting percentage (60%) was obtained with 1 mg L −1 of both IBA and NAA [20] and, lastly, Keresa and coworkers [25], working with wild bushes of C. orientalis, found that the rooting rate was equally efficient in the media supplemented with 2 mg L −1 of IAA or IBA, or in hormone-free rooting medium, whereas NAA at 2 mg L −1 was discarded due to the abundant callus formation on the induced roots.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations